2017
DOI: 10.1177/0268355517702057
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of clinical findings for the diagnosis of pelvic congestion syndrome in women with chronic pelvic pain

Abstract: Background Pelvic congestion syndrome is among the causes of pelvic pain. One of the diagnostic tools is pelvic venography using Beard's criteria, which are 91% sensitive and 80% specific for this syndrome. Objective To assess the diagnostic performance of the clinical findings in women diagnosed with pelvic congestion syndrome coming to a Level III institution. Methods Descriptive retrospective study in women with chronic pelvic pain taken to transuterine pelvic venography at the Advanced Gynecological Laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
(35 reference statements)
1
18
0
9
Order By: Relevance
“…Other common symptoms are lower extremity varicose veins (58.7 %), vulvar varicosities (45.9 %) and dyspareunia (40.8 %). In another study, in accordance with results of pelvic venography, clinical signs with the highest sensitivity for diagnosis of PCS are vulvar varicose veins (100 %), sensitivity of the ovarian region upon palpation (87 %), dysmenorrhea (84 %) and postcoital pain (79 %) [10]. It should be kept in mind that if patient also has a history of deep vein thrombosis in lower extremity, symptoms of PeVD may occur because of post-thrombotic syndrome caused by iliac vein obstruction [11].…”
Section: Diagnosissupporting
confidence: 54%
“…Other common symptoms are lower extremity varicose veins (58.7 %), vulvar varicosities (45.9 %) and dyspareunia (40.8 %). In another study, in accordance with results of pelvic venography, clinical signs with the highest sensitivity for diagnosis of PCS are vulvar varicose veins (100 %), sensitivity of the ovarian region upon palpation (87 %), dysmenorrhea (84 %) and postcoital pain (79 %) [10]. It should be kept in mind that if patient also has a history of deep vein thrombosis in lower extremity, symptoms of PeVD may occur because of post-thrombotic syndrome caused by iliac vein obstruction [11].…”
Section: Diagnosissupporting
confidence: 54%
“…Sensitivity to palpation of the ovaries and dyspareunia had 94% sensitivity and 77% specificity for PCS. 18 After ruling out other more common causes of chronic pelvic pain including endometriosis, pelvic inflammatory disease, interstitial cystitis, and leiomyomas, pelvic ultrasound is employed to view the gonadal vessels. 19 The association between PCS and lower limb venous insufficiency was demonstrated in a study conducted in Turkey, which showed that PCS was the cause of chronic pelvic pain in 30% of 100 consecutive patients, and that 70% of these cases also had symptoms of lower limb venous insufficiency, with reflux of the common femoral vein being the most frequent finding.…”
Section: Clinical Presentationmentioning
confidence: 99%
“… 15 Most of the signs and symptoms associated with venous-origin pelvic pain have been found to be relatively sensitive, but nonspecific. 19 Pelvic pain of venous origin is often characterized as dull unilateral or bilateral pain with occasional sharp flares. Bimanual examination, demonstrating focal adnexal tenderness, often reproduces the pain.…”
Section: Results: the Classification Of Pevdmentioning
confidence: 99%
“…Although deep dyspareunia is common among women with pelvic pain from a variety of causes, venous origin pain is more likely to be associated with prolonged postcoital ache. 12,15,19 The combination of postcoital ache and tenderness over the ovarian point (the junction of the upper and middle thirds of a line drawn from the umbilicus to the anterior superior iliac spine) has been reported to be 94% sensitive and 77% specific for distinguishing a venous origin from other causes of pelvic pain. 15 Although chronic pelvic pain also occurs in males, 20,21 there is currently little evidence to suggest that pelvic venous disease is an important contributing factor.…”
Section: Symptomsmentioning
confidence: 99%